Porcelain : A History from the Heart of Europe - Marchand, Suzanne L., 1961- (Book collections on Project MUSE., 2020)
"This is a history of porcelain as a business and consumer product, from the eighteenth century to the present day. Many books have been written on Chinese porcelain as an exotic import from Asia, but this book tells the history of the Central European reinvention and mass production of the material. Porcelain was first invented in medieval China, but the evolution of what its first producers called "white gold" was set in motion by Saxon king Augustus the Strong. Augustus obsessed over owning a personal alchemist, Johann Böttger, whom he imprisoned in his castle, first to make gold, and when that failed, to make porcelain. Trained in chemistry by an apothecary, Böttger took advantage of the king's obsession with porcelain and eventually produced the first European ceramic vessels whose delicacy and strength resembled those of Asian imports. Augustus funded the creation of a Saxon royal manufactory, which became the famous Meissen factory, and which to this day stands for the highest quality in porcelain. By the time of Böttger's death in 1719, Meissen porcelain had become famous throughout Europe and the world, its wares in high demand by other monarchs and aristocratic consumers. Soon after the porcelain maker's death, his secret recipe was stolen, and dozens of Central European princes opened their own manufactories. Here, author Suzanne L. Marchand shows how the story of European porcelain is an intertwined history of the mercantile state policy that built these factories, the luxury trades that sustained them, the debates about what counted as "art," and the changes in consumer and material culture driving the business. Throughout the eighteenth century, porcelain production was an industry of competitive, mercantile production under royal ownership. By 1850, however, after only a few state-backed firms survived the financial crises of 1815-1830, the Central European porcelain industry had become the domain of mass producers and trademark forgers. Marchand then traces the story of Central European porcelain into the twentieth century, exploring the new challenges of cartelization, the rise of Japanese and Czech competition, and the impact of the two world wars, following several porcelain firms through the Nazi era and the Russian seizures of companies in the German East. At each point, Marchand uses the history of porcelain to link the businesses, and the states that helped sustain them, to the broader history of culture and consumption"--